Rhizostomins: A Novel Pigment Family From Rhizostome Jellyfish (Cnidaria, Scyphozoa) - Lawley, Jonathan W.; Carroll, Anthony R.; McDougall, Carmel (Frontiers in Marine Science, 2021)
Many pigments, such as melanins, are widely distributed throughout the animal kingdom. Others have arisen as novelties in particular lineages, for example, the Green Fluorescent Protein (GFP) found in cnidarians. While GFPs, widely used as fluorescent tags in biomedical research, are the most famous cnidarian example, other novel proteins have also been identified within this phylum. A blue protein that contains a Kringle (KR) domain inserted within a Frizzled cysteine-rich domain (Fz-CRD) was previously described from the jellyfish Rhizostoma pulmo (named rpulFKz1), however little is known about this pigment’s evolution or distribution among cnidarians. We performed a systematic search for homologs of this protein in published genomes and transcriptomes of 93 cnidarians. Phylogenetic analyses revealed eight predicted proteins that possess both domains in the same arrangement and that fall within the same clade as rpulFKz1. The sequence of one of these proteins contains motifs that match sequenced peptides of Cassio Blue, the blue pigment from Cassiopea xamachana. Another one of these proteins belongs to Stomolophus meleagris, and chemical studies on blue pigments that may occur in this genus have shown similarities to rpulFKz1 and Cassio Blue. Therefore, we hypothesize that the eight rpulFKz1 homologs identified are also pigment precursors. All precursors identified were exclusive to jellyfish in the order Rhizostomeae, so we herein name this new pigment family “rhizostomins.” Not all rhizostomes analyzed are blue, however, so these rhizostomin proteins may also be responsible for other colors, or perform other biochemical and biophysical roles. Previous studies have hypothesized that cnidarian pigments are photoprotective, and this study serves as basis for future investigations not only on the function of rhizostomins, but also on potential biotechnological applications for these proteins.